Nationalism, imperialism, Machiavellianism.: Debates and controversies, decades 1880-1910 - Losada, Leandro (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2023)
The article studies a set of texts that, at the turn of the 19th century to the 20th, used Machiavelli to think about the main phenomena of Western politics at that time, nationalism and imperialism. The analysis of these texts allows us to study three problems, each one related to different historiographic productions: the reading traditions about the Florentine author and their changes through time; the relationship between nationalism and imperialism (especially German, considered by most of the authors chosen as an exemplary case of Machiavelli’s teachings); and the circulation of intellectual references, while the association between Machiavelli and imperialism was known and used by European, North American and Latin American authors.